A Scientific Approach-Based Digital Module for Biochemistry Learning in Biology Education: Development, Validation, and Evaluation of Effectiveness - Andi Tenri Ola Rivai; Zulkarnaim Zulkarnaim; Andi Citra Pratiwi (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
Biochemistry learning requires digital materials that can help students understand abstract concepts, molecular representations, and scientific processes more independently. This study aimed to develop and evaluate a scientific approach-based biochemistry e-module using the analysis, design, development, implementation, and evaluation model. The research employed a research and development design involving 35 Biology Education students, two lecturers, and two expert validators at UIN Alauddin Makassar. Data were collected through expert validation sheets, lecturer and student response questionnaires, and learning outcome tests administered before and after implementation. The data were analyzed descriptively using validity criteria, practicality percentages, mastery learning, and normalized gain. The results showed that the e-module obtained an overall validity score of 4.70 and was categorized as valid. Lecturer and student responses reached 89.70 percent and 90.38 percent, respectively, indicating very positive practicality. Student mastery increased from 5.71 percent before implementation to 88.57 percent after implementation, exceeding the classical mastery criterion. The average normalized gain was 0.71, indicating high learning improvement. These findings show that the scientific approach-based biochemistry e-module is valid, practical, and effective as a digital learning resource. The e-module supports structured content delivery, scientific learning activities, independent learning, and improved student understanding of biochemistry. The findings also suggest that scientific approach-based biochemistry learning may provide a conceptual foundation for subsequent learning in human anatomy and physiology